Advanced Oxidative Removal of Nitric Oxide from Flue Gas by Homogeneous Photo‐Fenton in a Photochemical Reactor. Issue 5 (5th April 2013) - Liu, Y.; Pan, J.; Du, M.; Tang, A.; Wang, Q.
Abstract In this work, advanced oxidation removal of nitric oxide (NO) from flue gas by homogeneous Photo‐Fenton was investigated in a photochemical reactor and the effects of several influencing factors on NO removal were evaluated. The gas‐liquid reaction products were determined. The reaction pathways of NO removal are also preliminarily discussed. It was found that with the increase of Fe2+ concentration, NO removal efficiency first increased and then decreased. Increasing H2O2 concentration and UV radiation intensity greatly increased NO removal efficiency, but the growth rates gradually became smaller. NO removal efficiency greatly reduced with the increase of gas flow and NO concentration, and only slightly decreased with the increase of solution temperature, but significantly increased with the increase of initial solution pH value. The main anion product in the liquid phase was NO3–. With respect to removal of NO using homogeneous Photo‐Fenton, ·OH oxidation was the main reaction pathway, and H2O2 oxidation was the secondary reaction pathway.